PENGARUH EKSTRAK TANAMAN SEBAGAI SUMBER ZPT ALAMI TERHADAP PERTUMBUHAN SETEK TANAMAN LADA (Piper nigrum L.) - Abdullah Abdullah; Mualana Wulandari; Nirwana Nirwana (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2019)
The purpose of research is to view the effect some crop extract as natural growth hormon towards pepper cutting growth, conduted in Bontomanai District of Selayar Island Regeny, during March – May 2018. This experimental research used random group of environmental design by one factor treatment, without Growth hormone submersion, coconut water 50%, red onion extract 75%, moringa leaves extract 30%, sargassum seaweed extract 25%, cow urine 15%, and Growtone 12,5%. The data was analyzed based on the F (ANOVA) test and contrast test. Growth hormone Growtone using is better than compared to coconut water, red onion, moringa leaves, sargassum seaweed and cow urine in responding, peper cutting growth. Red onion extract 75% is better than moringa leaves extract and sargassum seaweed extract towards to components of pepper cuttings growth (budding period, number of buds, bud length, root volume and the percentage of living cuttings) coconut water 50% has effect on budding period of pepper cuttings and cow urine 15% has effect on leaf wide. Sargassum extract 25% has effect on number of leaves and leaf wide.